2018
DOI: 10.2174/1570162x16666180502114344
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Drug Resistance Mutations Among the Dominant HIV-1 Subtype, CRF01_AE in Maumere, Indonesia

Abstract: CRF01_AE was the major HIV-1 subtype prevalent in Maumere. The appearance of drug resistance-associated mutations found in the present study supports the necessity of monitoring the effectiveness of ART in Maumere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
(43 reference statements)
2
16
1
Order By: Relevance
“…The pattern of resistance-associated mutations found in this study differs to that found in Maumere, East Nusa Tenggara, except for M184V [11]. This discrepancy might relate to the subject of the genotypic study.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…The pattern of resistance-associated mutations found in this study differs to that found in Maumere, East Nusa Tenggara, except for M184V [11]. This discrepancy might relate to the subject of the genotypic study.…”
Section: Discussioncontrasting
confidence: 91%
“…As expected, almost all of the HIV-1 identified individuals in this study harbored CRF01_AE subtype, which is the most common circulating subtype in Indonesia [9, 11, 24]. Only one was of A subtype.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Circulating recombinant form (CRF) 01_AE is one of the major CRFs of HIV-1 dominating the global epidemic and is prevalent throughout Southeast Asia. We previously reported that CRF01_AE was a dominant type of HIV-1 in Indonesia, while other subtypes and recombinants, including subtype B and the recombinant between CRF01_AE and subtype B, have emerged in Indonesia [2][3][4][5][6][7] .…”
Section: Textmentioning
confidence: 99%